Dialog Lintas Agama dalam Perspektif Hans Kung - Harjuna, Muhamad (Living Islam: Journal of Islamic Discourses, 2019)
This article discusses religious imperative in contributing to humanitarian problems, and is responsible for bringing about world peace. To make religion a source or principle to bring about peace, then it takes efort to dialog a religion with reality. In the case it will be discussed with a interreligious dialogue in the perspective of Hans Kung. According to Hans Kung, there is no world peace without the peace of religions. No peace of religions without a interreligious dialogue, and no interreligious dialogue without dives for the foundation of religions. The purpose of the interreligious dialogue according to Hans Kung is to reinvent religious souls so that it can be donated to various humanitarian problems. Hans Kung offered a constructive dialogue to built a consensus together with the purpose to create world peace. In the transition from the modern era to the postmodern era, Kung suggested a modern theological model called a critical ecumenical theology. Hans Kung also offers the importance of seeking a global ethic. Kung effort to set up a global ethic has a dual purpose, that is, to promote peace between religions and to “cure” the world that have a crisis of meaning, value, and norm. In addition, Kung also invited the religious people to make changes in the culture of the ko-existence to pro-existence. Kung also seeks to build a culture without violence. According to Hans Kung, the true religion is not only that does not conflict with humanity but also perfect humanity.